Fluid flow, energy transfer and design : special topic volume with invited peer reviewed papers only - Miguel, A. F. (António F.); Luiz Rocha, Miquel; Öchsner, Andreas (Diffusion and defect data. Defect and diffusion forum, 2014)
The special session ""Fluid Flow, Energy Transfer and Design"" held at the 9th International Conference on Diffusion in Solids and Liquids (DSL 2013) sheltered papers of different areas ranging from physics, mathematics and chemistry to engineering. It served as a link under which authors of different areas and backgrounds came together, and make their research accessible to the varied audience. In this sense worked to counter the possible divisive tendency. This special issue is a fitting tribute to the different views since this is not a divisive tendency but the seethe of science that shape.